Pengaruh Online Customer Review Terhadap Keputusan Pembelian Produk Body Lotion Scarlett Whitening Melalui E-Commerce Shopee @Scarlettofficialshop Pada Masyarakat Kota Cilegon - Bella, Bella; Mardiana, Siska; Pitasari, Dwi Nurina (Universitas Al Azhar Indonesia, 2023)
The background of this research is the emergence of e-commerce which is one of the causes of a shift in people's behavior that prefers shopping online, especially in Cilegon City who buy scarlett whitening body lotion through shopee @scarlettofficialshop. Online customer reviews on the shopee application @scarlettoffcialshop provide information about scarlett whitening body lotion products. The purpose of this study was to determine the presence and extent of the influence of online customer reviews at shopee @scarlettofficialshop on purchasing decisions for scarlett whitening body lotion products in Cilegon City. This study uses the elaboration likelihood model theory. This research approach uses a quantitative approach, and uses survey methods, the population of this study is the city of Cilegon as many as 450,271 people. The sample taken in this study was 400 respondents. The data analysis technique used is the classical assumption test, instrument test, simple linear regression analysis, determination coefficient, hypothesis testing. The results of this study can be seen that there is a positive and significant influence between online customer review variables and purchasing decision variables. And shows the value of Tcount > Ttable, namely 22.284 > 1.965, with a significance level of 0.000 <0.05. So it can be seen that there is a positive and significant influence between variable X (Online Customer Review) and variable Y (Purchasing Decision).